Identifying sustainability assessment elements: the case study of campus sustainability assessment elements for Universiti Kebangsaan Malaysia - Zuhair Fikri Fadzil,; Halimaton Saadiah Hashim,; Adi Irfan Che Ani,; Sarah Aziz Abdul Ghani Aziz, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
Sustainability Assessment Frameworks for any area must be unique to its characteristics. This study identifies campus sustainability assessment (CSA) elements for Universiti Kebangsaan Malaysia (UKM) or National University of Malaysia by examining established CSA frameworks, then adopting, and adapting suitable elements, thus avoiding starting from zero. The study explores CSA approaches and frameworks and then narrowed down to two approaches which are most comprehensive, namely the Campus Sustainability Assessment Framework (CSAF) and the Sustainability Tracking and Assessment Rating System (STARS). The study examines key aspects and elements in these frameworks, and then identifies relevant elements for the UKM CSA framework. This study finds that CSAF and STARS are most comprehensive and suitable. Their dimensions and aspects are different from UKM’s but their elements can match the Sustainable UKM Programme, thus suitable to be adopted and adapted by UKM. CSAF and STARS do not focus much on physical development as key aspects and elements. This is different from the UKM programme which gives a stronger focus on physical development. However most of the CSAF’s and STARS’ assessment elements are suitable for UKM. Using CSAF and STARS as a base for developing UKM’s sustainability assessment framework is regarded as appropriate as they are the most comprehensive methods and hence avoid starting from zero.